ADAPTATION OF WORK FROM HOME OR ANYWHERE IN THE HOSPITALITY AND TOURISM INDUSTRY IN YANGON AND MANDALAY, MYANMAR - Nway Nway Ei; Batra, Adarsh (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Due to the COVID-19 epidemic, every country announced the lockdown, travel restrictions, social distancing, curfew and stop gathering the people to prevent the spreading virus. The national government of Myanmar announced this policy in the month start of April 2020. Because of that policy, all of the business industry has to change its operation method. This study aims to know about the impact and challenges of work from home or anywhere and this method can be adapted in the hospitality industry or not. This research conducted a qualitative method and data was collected by using purposive sampling, in-depth interviews with 9 managers, and 1 employee from both of the destination Yangon and Mandalay hotels. The thematic method was used to analyze the data by coding the key information from the interview transcripts. This study finds that the people who work in work from home or anywhere method they got the opportunity to learn new things and leisure time not only that they also facing the problem of cannot working well like office and unbalancing work and live performance. The most challenging part of them is a technology and cannot bring out the data information from the organization. So, the people who work at hospitality industry is not easy to do work from home or anywhere like other organization and still need to go office also have to serve the customer with the human touch, warming and welcoming. Therefore no one thinks that working ways can be adapt but no one knows about the future. Keywords: Employee, Work from Home or Anywhere, Covid-19 epidemic, Hospitality and Tourism industry